Pengaruh Kualitas Sistem Manajemen Persuratan Terhadap Efisiensi dan Efektivitas di Sekolah - Z, Zulqaidah; Marpaung, Dian Pratiwi Br.; N, Nurroyian; Wardani, Tika Kesuma; Darmansah, T. (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
A quality correspondence management system can have a significant influence on the efficiency and effectiveness of school activities. This research uses a qualitative approach, which is also a literature study or library research method. Library institute research is because researchers need data from various literary sources, such as books and journals, to build a theoretical basis for the problem to be researched, namely “The Influence of the Quality of the Correspondence Management System on Efficiency and Effectiveness in Schools”. The aim of this research is to determine the basic concepts of the correspondence management system, the quality of the correspondence management system, the influence of the quality of the correspondence management system on efficiency and effectiveness in schools, and evaluate the effectiveness of archives governance as an effort to improve school performance. The research results show that efficiency can be achieved through a structured letter handling process, fast tracking and tracing capabilities of letters, as well as minimizing duplication or delays in handling letters. Meanwhile, effectiveness can be increased by ensuring compliance with regulations and policies related to records management, easy access to required information, and making appropriate decisions based on available data and information.